Transformations in the Couplings Among Intellectual Abilities and Constituent Cognitive Processes Across the Life Span - Li, Shu-Chen; Lindenberger, Ulman; Hommel, Bernhard; Aschersleben, Gisa; Prinz, Wolfgang; Baltes, Paul B. (Psychological Science, 2004)
Two-component theories of intellectual development over the life span postulate that fluid abilities develop earlier during child development and decline earlier during aging than crystallized abilities do, and that fluid abilities support or constrain the acquisition and expression of crystallized abilities. Thus, maturation and senescence compress the structure of intelligence by imposing age-specific constraints upon its constituent processes. Hence, the couplings among different intellectual abilities and cognitive processes are expected to be strong in childhood and old age. Findings from a population-based study of 291 individuals aged 6 to 89 years support these predictions. Furthermore, processing robustness, a frequently overlooked aspect of processing, predicted fluid intelligence beyond processing speed in old age but not in childhood, suggesting that the causes of more compressed functional organization of intelligence differ between maturation and senescence. Research on developmental changes in functional brain circuitry may profit from explicitly recognizing transformations in the organization of intellectual abilities and their underlying cognitive processes across the life span.